INTERNATIONAL EXPERIENCE IN THE DEVELOPMENT OF RECREATIONAL TOURISM - Polatova Mavluda Sanjar qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article provides a scientific analysis of international experience in the development of recreational tourism and evaluates the possibilities of its application in the conditions of Uzbekistan. During the research process, the experiences of countries with advanced recreational tourism sectors, such as Spain, Turkey, and Switzerland, were examined. It was revealed that in these countries recreational tourism has developed based on the effective integration of state policy, regional planning, infrastructure development, and private sector participation. The results of the analysis show that regional specialization, public-private partnership, investment incentive mechanisms, and principles of environmental sustainability play a significant role in the development of recreational tourism. At the same time, it was substantiated that foreign experience should not be directly copied but adapted to national economic and social conditions. Based on the findings of the research, scientific and practical recommendations were developed aimed at strengthening regional specialization, improving the investment environment, forming recreational tourism clusters, and ensuring ecological balance in the development of recreational tourism in Uzbekistan.